Parallel Aggregation on Sharded Clusters - Mothilal, T; P, Anil Kumar (International Journal of Computer Sciences and Engineering, 2025)
The data is organized by databases with the help of database management systems. DBMS is the collection of schemas, queries and other objects. To aggregate the data DBMS used Cartesian products between two or more tables and produce a result in a logical table. Where data is increasing rapidly day by day, so writing joins on large tables is difficult to data analysts and manage complex queries on large scale table is quite difficult to DBMS. To reduce complexity of manipulating large data schemaless databases are introduced. MongoDB process schemaless data and having more use cases to achieve parallel processing on data. Aggregation is one of the function which is applying on the data. To get fastest aggregation results use mongodb sharded cluster and mareduce.